Die natürliche Vegetation und ihre räumliche Ordnung im Puebla-Tlaxcala-Gebiet (Mexiko) - Klink, Hans-Jürgen (ERDKUNDE, 1973)
This paper, together with the accompanying map and the vegetation profile, provides a view of the three-dimensional spatial distribution of vegetation and the climatic and edaphic factors which determine it in the Puebla-Tlaxcala area of Mexico. Particular attention is paid to tree vegetation. To the south, the transition to the xerophytic warm tropical vegetation of the Balsas depression is traced. An introductory section gives a review of the altitudinal stages of vegetation on the humid eastern slopes of the Central Mexican Highlands from about 1,000 metres downward. Mexico is distinguished by a very species-rich vegetation. The ruchness of species is a consequence of the location of the country in the transitional area of the migration routes of two of the earth’s flora kingdoms. Boreal-nearctic flora elements which have migrated in from the north over the prominent Cordilleras since the Tertiary era, lie in layers over the tropical vegetation of the deeper parts of the country. In particular, the humid eastern slopes show a mixture of boreal-nearctic and tropical mountain and antarctic families from about 1,500 metres upwards. Of the latter only a few, forced into the undergrowth, are trying to penetrate the forests of the Highlands, dominated by boreal families. The plant-geographical boundary of the warm tropics with the tropical mountain deciduous forests in the south lies at around 1,800 metres. Although its course is deflected in individual instances by relief in association with local climatic influences, especially the presence of frosts. The vegetation units which have been described are ordered both climatically and edaphically. The climatic control is the overriding, more widely effective one. It is prominent especially in the altitudinal arrangement of vege tation and also in the effects of windward and lee positions. Edaphic effects, through the soil moisture regime and the mineral content of the substrata for soil formation, are especially important for special formations such as the gallery forests and also for the more detailed locational divisions within the climatic-ecologically determined vegetation units. The climatic types published by W. Lauer and E. Stiehl elsewhere in this issue are used for the climatic-ecological characterisation of plant communities. All the forests of the study area are being affected by strong destructive human intervention. One of the major future tasks for Mexico is reafforestation of the country in the interests of a functionally-effective environment: the prevention of further soil erosion, a balanced water regime, oxygen renewal and clean air.